Bio-equivalence study of two oral doxycycline formulations (doxycycline kela 75%® and mebcodox 75%®) in broiler Chickens - El-Komy, Ashraf; Aboubakr, Mohamed (International Journal of Pharmacology and Toxicology, 2020)
The present study was designed to assess the comparative bio-equivalence of Doxycycline Kela 75%® and Mebcodox 75%® in healthy broiler chickens after oral administration of both products in a dose of 20 mg doxycycline base/kg.b.wt. Twenty four broiler chickens were divided into two groups. The first group was designed to study the pharmacokinetics of Doxycycline Kela 75%®, while the 2nd group was designed to study the pharmacokinetics of Mebcodox 75%®. Each broiler chickens in both groups were orally administered with 20 mg doxycycline base/kg.b.wt. Blood samples were obtained from the wing vein and collected immediately before and at 0.08, 0.16, 0.25, 0.5, 1, 2, 4, 6, 8, 12 and 24 hours after a single oral administration The disposition kinetics of Doxycycline Kela 75%® and Mebcodox 75%® following oral administration of 20 mg doxycycline base/kg.b.wt. revealed that the maximum blood concentration [Cmax] were 3.35 and 3.28 μg/ml and attained at [tmax] of 0.97 and 0.99 hours, respectively.In conclusion: Mebcodox 75%® is bioequivalent to Doxycycline Kela 75%® since the ratios of Cmax, AUC0-24 and AUC0-∞ (T/R) was 0.97, 0.95 and 0.94 respectively. These are within the bioequivalence acceptance range. Mebcodox 75%® and Doxycycline Kela 75%® are therefore bioequivalent and interchangeable.
Keywords: Bioequivalence; Chickens; Doxycycline; oral; Pharmacokinetics.